Application of subthreshold laser therapy in retinal diseases: a review. (2nd November 2018) - Moore, Spencer M.; Chao, Daniel L.
ABSTRACT: Introduction: Laser photocoagulation has been a valuable tool in the ophthalmologist's armamentarium for decades. Conventional laser photocoagulation relies on visible retinal burns as a treatment end point, which is thought to result in photocoagulative necrosis of retinal tissue. Recent studies have suggested that using subthreshold (ST) laser, which does not cause detectable damage to the retina, may also have therapeutic effects in a variety of retinal diseases.Areas covered: We review the proposed biological mechanisms mediating the therapeutic effects of ST laser on the retina, followed by the evidence for ST laser efficacy in retinal diseases such as diabetic macular edema (DME), central serous chorioretinopathy, age-related macular degeneration, and retinal vein occlusion. Expert commentary: Multiple clinical studies demonstrate that ST laser does not cause structural damage to the retina based on multimodal imaging. Evidence suggests that there is a therapeutic effect on decreasing DME and subretinal fluid in chronic central serous retinopathy; however, the effect may be relatively modest and is not as efficacious as first-line treatments for these diseases. Given the repeatability and lack of damage to the retina by this treatment, ST laser deserves further study to determine its place in the retina specialist's armamentarium.